Middle to Late Pleistocene organic carbon and uranium content, nannofossil abundances and age model from IODP Site 356-U1460 - Gerald Auer; Benjamin F Petrick; Toshihiro Yoshimura; Briony L Mamo; Lars Reuning; Hideko Takayanagi; David De Vleeschouwer; Alfredo Martínez-García (PANGAEA, 2021)
Here we present records of International Ocean Discovery Program (IODP) Site U1460 (eastern Indian Ocean, 27°22.49'S, 112°55.42'E), including surface water productivity (alkenone abundances, total nannofossil as well as alkenone producing nannofossil abundances and accumulation rates), as well as relative abundances of small Gephyrocapsa spp. and Reticulofenestra asanoi, which were used in age model generation. Furthermore, we provide organic matter flux (total organic carbon and Uranium content and mass accumulation rates), as well as biogenic silica and terrigenous flux records in combination with bulk calcite equivalent calcium carbonate content. Absolute and relative Nannofossil data was generated using the drop technique (c.f. Bordiga et al., 2015, doi: 10.1016/j.revmic.2015.05.002), with mass accumulation rates calculated based on the attached age model. Bulk total and organic carbon content measured in a LECO CS300 carbonate and sulfur analyzer and calculated mass accumulation rates of organic carbon and the calcite equivalent carbonate content. Alkenone abundances and calculated accumulation rates are derived from data originally measured for Petrick et al. (2019, doi: 10.1038/s41598-019-53382-0). Shipboard whole round multi-senor logger natural gamma radiation derived U content (see De Vleeschouwer et al., 2017, doi:10.1002/2016gc0067159) and calculated U mass accumulation rates. X-ray fluorescence (XRF) derived element counts originally published in Petrick et al. (2019, doi: 10.1038/s41598-019-53382-0) are used to calculate log normalized multi-element ratios ln((Al+K)/Ca) and ln(Si/(Al+Ca)). The gathered proxy data covers the interval between 61 and 163 m CSF-A, corresponding to an age of 1.1 – 0.6 Ma, based on the attached age model. The data records Pleistocene Leeuwin Current dynamics and sea level-driven environmental changes along the West Australian shelf over the MPT.